Great South Gardens (Pacific Novelty Co.)
On verso: In the South Gardens the formal French treatment has been followed with most pleasing results. For the floral color effect which (thanks to the California climate) will be continuous from February to December, three plantings will be necessary, and for each of these about 200,000 plants will have to be ready.